Pengaruh Disiplin Kerja Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada PT F1 Logix Indonesia Cikarang Pusat - Yusuf Zuliansyah, Muhammad; Sopandi, Andi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstrak. This research aims to determine the influence of work discipline and physical work environment on employee performance at PT. F1 Logix Indonesia Central Cikarang. The research methodology used uses the associative method. The population in this study were all employees at PT F1 Logix Indonesia Central Cikarang, totaling 60 employees. The number of samples used in this research was 60 respondents using a saturated sampling technique. The data analysis method uses simple linear regression, multiple linear regression, correlation coefficient, coefficient of determination, partial t test and simultaneous F test. The research results show that there is a positive and significant influence of Work Discipline on employee performance at PT F1 Logix Indonesia Cikarang Pusat, this can be proven from the simple linear regression equation Y=15.474+0.416X. The correlation value is 0.669 (strong). The RSquare coefficient of determination value is 44.7%. The t value is 6.852 > t table 2.001 with a significance of 0.000 < 0.05. There is a positive and significant influence of the Physical Work Environment on employee performance at PT F1 Logix Indonesia Cikarang Pusat, this can be proven from the simple linear regression equation Y=13.994+0.447X. The correlation value is 0.689 (strong). The coefficient of determination value is 47.5%, the t value is 7.246 > t table 2.001 with a significance of 0.000 < 0.05. Simultaneously there is a positive and significant influence of Work Discipline and Physical Work Environment on employee performance at PT F1 Logix Indonesia Cikarang Pusat, this can be proven from the multiple linear regression equation Y=10.582+0.246X1+0.291X2. The correlation value is 0.758 (strong0. The coefficient of determination is 57.4%. The F value is 38.378 >F table 3.16 with a significance level of 0.000 < 0.05 Keywords: Work Discipline, Physical Work Environment, Employee Performance